Addition of ramucirumab enhances docetaxel efficacy in patients who had received anti-PD-1/PD-L1 treatment. (June 2020) - Tozuka, Takehiro; Kitazono, Satoru; Sakamoto, Hiroaki; Yoshida, Hiroshi; Amino, Yoshiaki; Uematsu, Shinya; Yoshizawa, Takahiro; Hasegawa, Tsukasa; Ariyasu, Ryo; Uchibori, Ken; Yanagitani, Noriko; Horai, Takeshi; et al.
Highlights: This study assessed the effect of ramucirumab on docetaxel after anti-PD-1/L1 therapy. Analysis using inverse probability of treatment weighting based on propensity scores. Ramucirumab enhanced docetaxel efficacy after anti-PD-1/L1 therapy. Docetaxel/ramucirumab is an effective treatment option after anti-PD-1/L1 therapy. Abstract: Objectives: : Docetaxel (DTX) efficacy increases in patients with non-small cell lung cancer (NSCLC) who had received anti-programmed cell death-1/ligand 1 (anti-PD-1/L1) therapy. However, the effect of ramucirumab (Ram) on DTX efficacy following anti-PD-1/L1 therapy is unknown. Here, we aimed to evaluate the effect of Ram on DTX efficacy following anti-PD-1/L1 therapy. Materials and methods: This retrospective study included 99 patients with NSCLC, who were divided into those who had (pre-ICI group) or had not (no-ICI group) received anti-PD-1/L1 antibody before DTX. Both groups were then treated with DTX or DTX plus Ram (DTX/Ram). Patient characteristics were compared between the DTX and DTX/Ram groups and adjusted with inverse probability of treatment weighting using propensity scores and the following confounding variables: age, sex, performance status, smoking status, histology, driver mutation, and line of treatment. We compared DTX/Ram and DTX in terms of efficacy in both the pre-ICI and no-ICI groups. Results: In the pre-ICI group, 18 and 21 patients received DTX and DTX/Ram, respectively. In the no-ICI group, 35 and 25 patients received DTX and DTX/Ram. In the no-ICI group, progression-free survival (PFS) and overall survival (OS) were not significantly different between DTX/Ram- and DTX-treated patients (median PFS, 2.6 versus 1.6 months; p  = 0.30, median OS; 8.2 versus 8.0 months; p  = 0.30). In the pre-ICI group, PFS was significantly longer in DTX/Ram-treated than in DTX-treated patients (median, 5.9 versus 2.8 months; p  = 0.03). Hazard ratio for disease progression or death was 0.75 (95% confidence interval, 0.20–0.96). The OS of DTX/Ram-treated patients tended to be longer than that of DTX-treated patients (median, 19.8 versus 8.6 months; p  = 0.10). Conclusions: DTX efficacy following anti-PD-1/L1 therapy may be enhanced by Ram. Further studies are needed to validate the efficacy of inhibiting the vascular endothelial growth factor pathway following anti-PD-1/L1 therapy.